A multifactorial approach employing melatonin to accelerate resynchronization of sleep-wake cycle after a 12 time-zone westerly transmeridian flight in elite soccer athletes - Cardinali, D. P.; Bortman, G. P.; Liotta, G.; Lloret, S. P.; Albornoz, L. E.; Cutrera, R. A.; Batista, J.; Gallo, P. O. (2002)
Rapid transmeridian translocation through multiple time zones has a negative impact on athletic performance. The aim of the present study was to test the timely use of three factors (melatonin treatment, exposure to light, physical exercise) to hasten the resynchronization of a group of elite sports competitors and their coaches to a westerly transmeridian flight comprising of 12 time-zones. Twenty-two male subjects were included in the study. They were professional soccer players and their coaches who travelled to Tokyo to play the final game of the Intercontinental Coup. The day prior to departure, urine was collected from each subject from 18:00 to 06:00 hrs to measure the melatonin metabolite 6-sulphatoxymelatonin. Participants were asked to complete sleep log diaries from day 0 (preflight) to the day before returning to Buenos Aires (day 8). All subjects received 3 mg of melatonin p.o. daily at expected bedtime at Tokyo immediately after leaving Buenos Aires. Upon arrival at Tokyo the subjects performed a daily physical exercise routine outdoors at two restricted times of the day (from 08:00 to 11:00 hrs in the morning and from 13:00 to 16:00 hrs in the afternoon). Exposure to sunlight or physical exercise at other times of the day was avoided. Except for the number of awakenings (which increased on days 1 and 3) and sleep latency (which decreased on days 2, 6 and 8), there was an absence of significant changes in subjective sleep parameters as compared with preflight assessment. Sleep quality and morning alertness at Tokyo correlated significantly with preflight 6-sulphatoxymelatonin excretion. Mean resynchronization rate of sleep--wake cycle to the 12 hr-time shift was 2.13 [plus minus] 0.88 days, significantly different from the minimal resynchronization rate of 6 days expected after a 12-time-zones flight. The results indicate that the combination of melatonin treatment, an appropriate environmental light schedule and timely applied physical exercise can be useful to help elite athletes to overcome the consequences of jet lag. J Pineal Res 2002 Jan;32(1):41-46